2013
DOI: 10.1016/j.jvb.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to change: The value of change information and meaning-making

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 46 publications
2
99
0
1
Order By: Relevance
“…For Study 2, four-items were formulated to assess whether nurses completed a screening checklist (e.g., "I use the checklist in the care chart") that was developed based on organizational interviews and in line with Griffin, Neal, and Parker (2007). This measure is valid and reliable (Van den Heuvel, Demerouti, Bakker, & Schaufeli, 2013); the scales ranged from 1 (strongly disagree) to 6 (strongly agree; Study 1), and 1 (never) to 5 (extremely often; Study 2).…”
Section: Adaptive Performancementioning
confidence: 99%
“…For Study 2, four-items were formulated to assess whether nurses completed a screening checklist (e.g., "I use the checklist in the care chart") that was developed based on organizational interviews and in line with Griffin, Neal, and Parker (2007). This measure is valid and reliable (Van den Heuvel, Demerouti, Bakker, & Schaufeli, 2013); the scales ranged from 1 (strongly disagree) to 6 (strongly agree; Study 1), and 1 (never) to 5 (extremely often; Study 2).…”
Section: Adaptive Performancementioning
confidence: 99%
“…Participation itself is potentially a type of collective coping strategy (Kuo, 2013), which can further manage job insecurity during restructuring. More information about the change process is likely to be provided during the discussions and intervention activities, which can make the restructuring process more comprehensible (van den Heuvel, Demerouti, Bakker, & Schaufeli, 2013). The collective job crafting and empowerment aspects of an intervention may also foster a proactive stance towards restructuring.…”
Section: Theoretical Framework For the Interventionmentioning
confidence: 99%
“…McMillan, O Driscoll, and Burke (2003) identified both behavioral and cognitive components of workaholism where the behavioral component was operationalised as a strong irresistible inner drive and working excessively hard, while the cognitive component was evident in thinking persistently about work, and working compulsively. Van Beek, Hu, Schaufeli, Taris, and Schreurs (2012) found that high levels of workaholism were associated with high levels of introjected regulation (controlled extrinsic motivation where individuals act to avoid criticism or to receive reward) combined with high levels of identified regulation (autonomous extrinsic motivation where individuals accept and identify with the reasons to act). This definition is adopted by Schaufeli, Shimazu, and Taris (2009) who define workaholism as "the tendency to work excessively hard (behavioral dimension)" and describe workaholics as "being obsessed with work (cognitive dimension), which manifests itself in working compulsively" (p. 322).…”
Section: Employee Well-being and Ill-being: A Taxonomymentioning
confidence: 99%